Taxing Sugar-Sweetened Beverages and Its Impact on Children’s Consumption: A Cross- Sectional Study among a Group of Children in Jeddah city - K. Baghlaf, Khoold (Journal of King Abdulaziz University: Medical Sciences, 2021)
Sugar-sweetened beverages (SSBs) are beverages with added sugars; they include, but are not limited to, soft drinks, fruit juices and drinks, and flavored milk. In 2019, the General Authority of Zakat and Tax announced the application of a 50% excise tax on SSBs in Saudi Arabia. This study aims to evaluate the consumption of sugar-sweetened beverages and the effect of taxing consumption patterns among a group of 6- to 11-year- old children attending King Abdulaziz University Faculty of Dental Hospital (KAUFD) Clinics in Jeddah, Saudi Arabia. This cross-sectional study involved randomly selected parents of 6- to 11-year-old children attending KAUFD for dental treatment. It used a validated Arabic questionnaire, and 128 parents were included. The most common source of SSBs is fruit juices and drinks; 46 (35.9%) participants reported that their children switched to untaxed drinks after taxing. Significantly more children from families with low monthly family income switched to an untaxed product compared to families with high monthly family income (P-value of 0.023). The consumption of sugar- sweetened beverages is relatively high among children in the KAUFD, and fruit juices and drinks are the most commonly consumed SSBs. The effect of tax implementation is more noticeable in the consumption pattern of children from families with low monthly income.